2021
DOI: 10.1590/1677-5449.200188
|View full text |Cite
|
Sign up to set email alerts
|

Identificação pela ultrassonografia vascular da compressão da veia ilíaca comum esquerda em mulheres assintomáticas: ortostatismo pode influenciar o diagnóstico?

Abstract: Resumo Contexto A ultrassonografia vascular é o exame de imagem de escolha para rastreamento inicial da compressão na veia ilíaca comum esquerda, cujo achado assintomático pode ser encontrado em até 25% em algumas casuísticas. Objetivo Identificar, pela ultrassonografia vascular, se há diferença na avaliação da compressão na veia ilíaca comum esquerda em mulheres assintomáticas em decúbito dorsal e ao ortostatismo. Métodos Trata-se de um estudo observacional transversal em 50 mulheres voluntárias, sem sinto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Furthermore, the spermatic vein in patients with (suspected) varicocele increased in diameter in upright relative to supine position [19][20][21]. The common iliac vein diameter increased in R-TB [22] and upright position [23,24]. For the right hepatic vein and portal vein dimensions, no correlation was found between supine and TB positions [26].…”
Section: Abdomenmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the spermatic vein in patients with (suspected) varicocele increased in diameter in upright relative to supine position [19][20][21]. The common iliac vein diameter increased in R-TB [22] and upright position [23,24]. For the right hepatic vein and portal vein dimensions, no correlation was found between supine and TB positions [26].…”
Section: Abdomenmentioning
confidence: 93%
“…In the abdominal region, US was the most frequently reported imaging modality in different body postures and positions with 13 out of 19 articles [15][16][17][18][19][20][21][22][23][24][25][26][27]. Of these thirteen studies, the majority focused on the inferior vena cava (IVC) diameter that increased when going from supine to prone position by approximately 0.2 cm [15] and increased further with 0.2 cm from prone to standing position [27].…”
Section: Abdomenmentioning
confidence: 99%
“…To elucidate the mechanism by which IVCS predisposes patients to venous thrombosis, several studies have investigated the effect of IVCS on iliac vein hemodynamics. Ultrasound studies have demonstrated that anatomical compression of the LCIV increases post-stenotic blood velocities by as much as 3-8x (Labropoulos et al, 2007;Oğuzkurt et al, 2007;Cheng et al, 2017;Engelhorn et al, 2021). Computational fluid dynamics studies have further demonstrated that IVCS leads to increased blood velocities, wall shear stresses, and pressure gradients in the stenosed vessel (Wang et al, 2022;Assi et al, 2023;Li et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Echo-Doppler velocimetric parameters of a mature AVF are vein diameter greater than 6 mm, fistula flow greater than 600 mL/min, and vein depth in relation to the dermal surface of less than 6 mm. 4,8 AVF dysfunctions can be stenotic (thrombosis or hemodynamically significant stenosis) or non-stenotic (steal syndrome, pseudoaneurysm, hematoma, or infection). 3 CVC is an alternative access, preferably tunneled, and it is acceptable to use non-tunneled CVC for up to 2 weeks.…”
Section: Introductionmentioning
confidence: 99%